PdpC, a secreted effector protein of the type six secretion system, is required for erythrocyte invasion by Francisella tularensis LVS - Cantlay, Stuart; Kaftanic, Christian; Horzempa, Joseph (Frontiers in Cellular and Infection Microbiology, 2022)
Francisella tularensis is a gram negative, intracellular pathogen that is the causative agent of the potentially fatal disease, tularemia. During infection, F. tularensis is engulfed by and replicates within host macrophages. Additionally, this bacterium has also been shown to invade human erythrocytes and, in both cases, the Type Six Secretion System (T6SS) is required for these host-pathogen interaction. One T6SS effector protein, PdpC, is important for macrophage infection, playing a role in phagolysosomal escape and intracellular replication. To determine if PdpC also plays a role in erythrocyte invasion, we constructed a pdpC-null mutant in the live vaccine strain, F. tularensis LVS. We show that PdpC is required for invasion of human and sheep erythrocytes during in vitro assays and that reintroduction of a copy of pdpC, in trans, rescues this phenotype. The interaction with human erythrocytes was further characterized using double-immunofluorescence microscopy to show that PdpC is required for attachment of F. tularensis LVS to erythrocytes as well as invasion. To learn more about the role of PdpC in erythrocyte invasion we generated a strain of F. tularensis LVS expressing pdpC-emgfp. PdpC-EmGFP localizes as discrete foci in a subset of F. tularensis LVS cells grown in broth culture and accumulates in erythrocytes during invasion assays. Our results are the first example of a secreted effector protein of the T6SS shown to be involved in erythrocyte invasion and indicate that PdpC is secreted into erythrocytes during invasion.